Health counselling as an effort to improve knowledge of female reproductive health in school-age children - Yeccy Anggreny; Erianti, Susi; Hamid, Abdurrahman; Niriyah, Sekani (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Puberty is one of the developmental phases that we will go through. Hormonal changes and maturity of human reproductive functions begin at this stage. Reproductive health is one of the things that is still taboo to be given early in Indonesia. Children seek information through friends, the internet and social media. The incidence of premarital pregnancy, promiscuous sexual behaviour and sexual violence are forms of problems that arise along with the lack of knowledge of children about reproductive health. The purpose of this service activity is to provide knowledge to students about reproductive health. The method used is by providing health counselling and students are also equipped with lefleat. There was an increase in knowledge before and after this activity took place.